Individual variables with an impact on knowledge sharing: the critical role of employees' ignorance. Issue 6 (12th October 2015) - Israilidis, John; Siachou, Evangelia; Cooke, Louise; Lock, Russell
Abstract : Purpose: – The purpose of this paper is to identify individual variables with an impact on knowledge sharing and explore the under-discussed construct of employees' ignorance. This can enhance the knowledge-sharing process and facilitate the development of greater intellectual capital. Design/methodology/approach: – Eighty-four dependent variables affecting knowledge sharing are analyzed and classified into 11 categories. In addition, the direct effect of employees' ignorance on knowledge sharing is introduced and empirically investigated in a case study of a multinational organization operating within the aerospace and defense industry. Findings: – The findings suggest that employees' ignorance may negatively affect their intention to share knowledge, thus leading to poor decision-making and communication in organizations. Employees' ignorance could also limit the organizational ability to repel external threats, implement innovation and manage future risks. Originality/value: – A classification scheme based on different categories of employees' ignorance is developed, providing tailor-made recommendations for practitioners facing different types of ill-informed organizational scenarios. Further, the need to shift the emphasis away from the management of knowledge to the management of ignorance is also an important contribution of this paper.